2015
DOI: 10.1186/s13037-015-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey on surgeons' perceived quality of the informed consent process in a Swiss paediatric surgery unit

Abstract: AimTo evaluate the levels of satisfaction and opinions on the usefulness of the informed consent form currently in use in our Paediatric Surgery Department.Materials and methodsDesign: Qualitative study carried out via interviews of senior paediatric surgeons, based on a questionnaire built up from reference criteria in the literature and public health law.ResultsPhysicians with between 2 and 35 years experience of paediatric surgery, with a participation rate of 92 %, agreed on the definition of an informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Informed medical consent is crucial and goes far beyond signing a form [ 5 ]. Nowadays this is put more to the physicians’ attention because of a dramatic emergence in medico legal processes [ 6 ]. Joolaee S. et al reported that 48 % of the patients did not even read the form before signing [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Informed medical consent is crucial and goes far beyond signing a form [ 5 ]. Nowadays this is put more to the physicians’ attention because of a dramatic emergence in medico legal processes [ 6 ]. Joolaee S. et al reported that 48 % of the patients did not even read the form before signing [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…(12) Many patients have limited understanding about the implications of the FICF, and are unable to understand that the document protects their interests and enables them to exercise autonomy. (13) In this study, it was found that the vast majority of participants agreed that the FICF had plain language and clear information. This is in contrast to another study, in which the FICF presented a high degree of difficulty reading.…”
Section: Discussionmentioning
confidence: 68%
“…One of the reasons reported for not reading and only signing the FICF without requesting explanation of the information contained in it were: fear of reading it and finding out the risks that they would be subject to, hurry to complete the bureaucratic part of hospitalization to perform the procedure as soon as possible, and fear of not signing and not being cared for or operated on, among other factors listed as the reason to merely sign it (without reading). (13) On the basis of their higher level of knowledge, it is possible that the physician implicitly exercises on their patient an involuntary psychic duress, making the patient feel embarrassed to read the document and sign it anyway. (21) When asked if they knew the function of the FICF, 28.9% disagreed.…”
Section: Discussionmentioning
confidence: 99%